ANALISIS UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE, DAN DPR TERHADAP PERATAAN LABA - Rendy Lanang Galih Gumilang, 09.05.52.0026; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2013)
The research itâs about to examine the influence company size, profitability, Financial Leverage, and Dividen Payout Ratio, toward income smoothing to manufaktur company which is registered in BEI. Company size dividend with using natural logaritma total asset. Profitabilty dividend with ratio between tax profit with asset totaly. Financial leverage dividend with ratio debt total with asset total, and dividen payout ratio dividend with each of sheet share toward profit each of sheet share.Income smoothing dividend with using Wang and Williams method. The populations from this research are 148 manufaktur companies resgistered in BEI for 2009- 2011 period. The data from this research to get from Indonesia Capital Market Directory (ICMD). According purposive sampling method, sampel to get 15 companies. In examined this hipotesis dividend using logistic regresi analize.The analize proceeds to show that it has significant influence toward income smoothing are profitability and financial leverage. And then variable company size and dividen payout ratio are not influences to profit balancing significantly.Keywords: company size, profitability, financial leverage, dividen payout ratio, and income smoothing.